Innovation in prediction planning for anterior open bite correction - Almuzian Mohammed; Almukhtar Anas; O'Neil Michael; Benington Philip; Al Anezi Thamer; Ayoub Ashraf (Sciendo, 2015)
This study applies recent advances in 3D virtual imaging for application in the prediction planning of dentofacial deformities. Stereo-photogrammetry has been used to create virtual and physical models, which are creatively combined in planning the surgical correction of anterior open bite. The application of these novel methods is demonstrated through the surgical correction of a case.